SUKU BALSAMINACEAE DI JAWA: STATUS TAKSONOMI DAN KONSERVASINYA - Utami, Nanda (BERITA BIOLOGI, 2014)
Study on the taxonomy and conservation status of Balsaminaceaein Java has been carried out. Based on the literature study, herbarium specimen deposited at Herbarium Bogoriense-LIPI (BO) and several field works in Java, there were two genera of Balsaminaceae found in Java namely, the monotypic Hydrocera triflora and the prolific Impatiens. The Impatiens consisted of seven species, i.e. Impatiens arriensii, I. chonoceras, I. radicans, I. javensis, I. wallerana, I. Platypetala and I. balsamina. Three species among them, Impatiens arriensii, I. radicans and I. Chonoceras were endemic and threatened in their habitat, while I. microceras has been extinct in the wild.The species Impatiens arriensiiwas transferred from the genus Semeiocardium.